2019
DOI: 10.7150/ijbs.30099
|View full text |Cite
|
Sign up to set email alerts
|

EBV miR-BART10-3p Promotes Cell Proliferation and Migration by Targeting DKK1

Abstract: In Epstein-Barr virus (EBV)-infected epithelial cancers, BamHI A rightward transcript (BART) miRNAs are highly expressed. However, only a few target genes of BART miRNAs have been investigated. Our mRNA microarray data showed that DKK1 was markedly down-regulated in EBV-associated gastric carcinoma (EBVaGC) cells. Using luciferase reporter assay we tested whether miR-BART10-3p regulates DKK1 by directly targeting the 3'-UTR of DKK1 mRNA. We observed that miR-BART10-3p transfection decreased DKK1 expression, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…showed that miR-BART7 promoted anchorage-independent growth. Additionally, several studies showed that BART miRNAs promoted cell migration [54,55]. Based on our KLF2 knockdown and overexpression data, the phenotype induced by miR-BART17-5p may be due to the decreased expression of KLF2.…”
Section: Discussionsupporting
confidence: 55%
“…showed that miR-BART7 promoted anchorage-independent growth. Additionally, several studies showed that BART miRNAs promoted cell migration [54,55]. Based on our KLF2 knockdown and overexpression data, the phenotype induced by miR-BART17-5p may be due to the decreased expression of KLF2.…”
Section: Discussionsupporting
confidence: 55%
“…The EBV genome contains two regions that encode more than 40 miRNAs that regulate the expression of viral and human genes, such as ebv-miR-BART-1-3p, -2-5p, -3-3p, -4-5p, -5-5p, -7-3p, -9-3p, -10-3p, -17-5p, -10-3p, -18-5p, BART11, etc. (62)(63)(64)(65)(66)(67). Studies suggest that EBV miRNAs affect immune response and antigen presentation and recognition, alter the communication between T-and B-cells, drive the production of antibodies during infection, and play a role in apoptosis.…”
Section: Micrornasmentioning
confidence: 99%
“…These miRNAs are differentially expressed in different cell types and latencies, which have been extensively studied in lymphoma and carcinoma [ 9 11 ]. Emerging findings suggest that EBV's miRNAs are involved in regulating innate and adaptive immune responses, cell proliferation and apoptosis, and tumor metastasis [ 12 14 ]. EBV-derived noncoding RNAs especially miRNAs can also transfer through exosome and regulate the function for the tumorigenesis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%